2011
DOI: 10.1017/s1041610211001700
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between gender, age, family conditions, physical and mental health, and social isolation of elderly caregivers

Abstract: Gender roles, age, income and social support interacted with physical and emotional health, and with the continuity of social participation of elderly caregivers. Special attention must be given to male caregivers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
70
1
11

Year Published

2015
2015
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(91 citation statements)
references
References 29 publications
(63 reference statements)
7
70
1
11
Order By: Relevance
“…Regarding the sociodemographic characteristics of the participants, this study observed that the elderly caregivers are mainly female aged between 60 and 75 years, with low income and married/with a partner; a profile similar to that found in other studies (2)(3)27) . Women are the main executors of informal care for family members, reinforcing the historically attributed role of women with the function of providing care for the home, children and the family (13,27) .…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Regarding the sociodemographic characteristics of the participants, this study observed that the elderly caregivers are mainly female aged between 60 and 75 years, with low income and married/with a partner; a profile similar to that found in other studies (2)(3)27) . Women are the main executors of informal care for family members, reinforcing the historically attributed role of women with the function of providing care for the home, children and the family (13,27) .…”
Section: Discussionsupporting
confidence: 86%
“…Several studies indicate that family members are the main caregivers for the elderly, however, with the demographic transition and changes in family dynamics, the number of older persons who perform the role of primary caregiver of another elderly family member has increased over the years (1)(2) . By taking on the responsibility of providing care, caregivers can modify their life routine, they increase their work overload and become more susceptible to the presence of comorbidities, with chronic pain being among them (2)(3) .…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of frailty ranges from 5.2% to 48% based on Fried criteria in studies including large populations (18,19). Collard et al determined the general prevalence to be 10.7% within the scope of a systematic review (20).…”
Section: Discussionmentioning
confidence: 99%
“…A institucionalização pode produzir um distanciamento progressivo da família em relação ao idoso, conduzindo em alguns casos a situações de abandono. No entanto, dependendo da estrutura, do contexto e da dinâmica familiar em que vive o idoso, a ILP assume uma função importante de reintegração social (3,4) .…”
Section: Introductionunclassified